Teaching and Translation Problems For Students in The Fourth Semester of Islamic Boarding School Darussalam For Girls Campus 1 - Abdul Hafidz Zaid; Siti Djunnuraini Binti Djaidin (Educan : Jurnal Pendidikan Islam, 2019)
Tarjamah is one of the subject taught in Islamic Training Teacher College Modern Islamic Boarding School Gontor One For Girls. According to the purposeof it learning, this subject enters into Diraasaah Islamiyyah field. But since theholding of the revision, Tarjamah especially as the subject of class four with specialbook and Nahwu Al-Wadih book systematics complete with the rule of translationwith examples and exercises can be entered into Dirasah Lughowiyyah field.Therefore curriculum staff Islamic Training Teacher College Modern IslamicBoarding School hopes to the teacher of Tarjamah is the teacher with anaccomplished expert in the field of Arabic language such as Nahwu, Shorf andBalaghah not the contrary nor just teachers where possible to teach. In the processof teaching and learning which has lasted for tarjamah around four years with hernew material found numerous problems, especially problems in his teaching.